Trauma Embolization: A Review of Embolic Agents - Wiechecki, Baylee A.; Quencer, Keith B.; Tavri, Sidhartha (Digestive Disease Interventions, 2025)
Transcatheter embolization is integral to the management of trauma-related hemorrhage. Various traditional and newer embolic agents, such as Gelfoam, coils, plugs, liquids, and conformable agents, have been utilized to achieve adequate hemostasis in trauma. This overview of various embolic agents may help the interventional radiologist choose the best embolic agent in the trauma setting.
Keywords: trauma; embolization; interventional radiology